2016
DOI: 10.1080/21641846.2016.1236588
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in patients with myalgic encephalomyelitis and chronic fatigue syndrome

Abstract: Background-There is a dearth of research examining mortality in individuals with myalgic encephalomyelitis (ME) and chronic fatigue syndrome (CFS). Some studies suggest there is an elevated risk of suicide and earlier mortality compared to national norms. However, findings are inconsistent as other researchers have not found significant increases in all-cause mortality for patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 82 publications
(79 reference statements)
0
37
0
3
Order By: Relevance
“…In addition to the increased mortality due to these causes, the 2006 Jason and 2016 McManimem studies also reported that these deaths occurred at a significantly earlier age than normal [31,33].…”
Section: Usmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to the increased mortality due to these causes, the 2006 Jason and 2016 McManimem studies also reported that these deaths occurred at a significantly earlier age than normal [31,33].…”
Section: Usmentioning
confidence: 99%
“…However, one of the criteria used to select y = 107326x 0.5541 $1,000,000 $10,000,000 $100,000,000 $1,000,000,000 $10,000,000,000 1,000 100,000 10,000,000 patients in this study required only six months of chronic fatigue for which there was no medical explanation [36]. As McManimen noted, use of these criteria could have included patients who do not have ME/ CFS and could have also included more patients suffering instead from a mental illness, either of which could have resulted in skewed findings [33].…”
Section: Estimating Yllmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies examining mortality among individuals with ME and CFS have found an increased risk of early mortality with cancer, cardiovascular issues, and suicide (Jason, Corradi, Gress, Williams, & Torres‐Harding, ; Jiménez‐Ortiz, ; McManimen et al., ; Roberts, Wessely, Chalder, Chang, & Hotopf, ). For example, Roberts et al.…”
mentioning
confidence: 99%